Analisis Pengukuran Kinerja Perusahaan menggunakan Metode SMART System - Nisak, Khoirotun; Iriani, Iriani (Fakultas Ekonomi Universitas Samudra, 2023)
The research aims to analyze company performance using the SMART system method at PT. Mohtra Agung Persada. Data processing in this quantitative research was carried out by weighting using the AHP model, then a scoring system with an objective matrix (OMAX) and determining color indicators using a traffic light system (TLS). The results found that the overall performance of PT Mohtra Agung Persada is considered to be in the yellow category, so the company needs to make efforts to improve the performance. Based on the identification results of 20 key performance indicators (KPI), it was found that 10 KPIs were in the green category, while the other 5 KPIs each were in the yellow and red categories. This indicates the performance of PT. Mohtra Agung Persada still needs improvement.